2010
DOI: 10.1111/j.1442-2042.2010.02448.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal parenchymal thickness and urinary protein levels in patients with ureteropelvic junction obstruction after nephrostomy placement

Abstract: Objective: To assess recovery of renal parenchymal thickness and urinary protein levels in patients with severely hydronephrotic kidneys after nephrostomy placement. Methods: Fourteen patients (median age 1 year, range 6 months-7 years) who underwent nephrostomy placement for unilateral ureteropelvic junction obstruction at our hospital between May 2007 and January 2009 were included in a retrospective analysis. All patients had severe hydronephrosis, with a median parenchymal thickness of 1.8 mm (range 1-2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…It was suggested that persistent obstruction is associated with severe glomerular membrane damage, resulting in lower leakage of larger proteins, yet, higher leakage of smaller proteins. However, nephrotic syndrome was not reported in these children . In conclusion, unilateral partial UPJ obstruction can be a cause of full‐blown nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It was suggested that persistent obstruction is associated with severe glomerular membrane damage, resulting in lower leakage of larger proteins, yet, higher leakage of smaller proteins. However, nephrotic syndrome was not reported in these children . In conclusion, unilateral partial UPJ obstruction can be a cause of full‐blown nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 73%
“…However, nephrotic syndrome was not reported in these children. 2 In conclusion, unilateral partial UPJ obstruction can be a cause of full-blown nephrotic syndrome.…”
mentioning
confidence: 92%
“…In the literature, there are some studies reporting that a 4-week follow-up might be sufficient to evaluate the recovery of renal functions. Deng et al (22) evaluated improvement of renal function in patients with ureteropelvic junction obstruction after insertion of nephrostomy and reported that paranchymal thickness increases in 4 weeks and tubular function returns to nearly normal levels in this period. In another study, Shokeir et al (20) evaluated renal resistive index and reported that at the first week of relief of obstruction, the mean resistive index significantly decreased and stabilized till to the 4 th week.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that urinary tract obstruction may occasionally cause proteinuria outside of pregnancy is well known, even if not frequently reported [9-11]; its degree is usually sub-nephrotic and its pathogenesis is usually related to increased pressure in the renal pelvis, leading to a diuretic response from the contralateral kidney. Proteinuria caused by kidney obstruction is usually mild and considered of tubular origin, although different mechanisms may be operating [12,13].…”
Section: Introductionmentioning
confidence: 99%